Rancang Bangun Prototype Aplikasi Koperasi Mahasiswa B-IU Digicoop Untuk Pencapaian Inklusi Keuangan Nusantara - Muhammad Alfarizi; Deby Gita Anggraeni; Almayda Andriana Firmansyah; Ngatindriatun Ngatindriatun (Jurnal JEETech, 2023)
The COVID-19 pandemic has paralyzed the economy both nationally and internationally. Various business sectors have experienced a slowdown due to the COVID-19 pandemic, one of the financial institutions affected by COVID-19 is cooperative. Currently, Student Cooperatives are required to be agents of change and can contribute positively to society in particular and the Indonesian state, especially in the post-pandemic national economic recovery. The B-IU Digicoop application was developed to unite the strength of Student Cooperatives throughout Indonesia to empower cooperatives in community economic activities, especially students and local residents to help with economic recovery after the Covid-19 pandemic while responding to the challenges of the times in order to achieve the hopes of student cooperatives continuing to transform. become the energy of change for the progress of Indonesian cooperatives in the future. This research uses the R&D method by optimizing the prototype design. The results of this study show the flow of prototype development to take into account the impact of innovation and replication opportunities in the community with the hope of helping economic recovery after the Covid-19 pandemic while responding to the challenges of the times in order to achieve the hope that student cooperatives will continue to transform into energy of change for the progress of Indonesian cooperatives. futile in the future. Indonesia's financial inclusion is expected to increase further with the presence of the B-IU Digicoop application